ANALISIS HASIL BELAJAR OPERASI BILANGAN BULAT DENGAN MEDIA KARTU DOMINO PADA SISWA SEKOLAH DASAR - Yunda Ayunningtias; Asep Sahrul Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low achievement of elementary school students in mathematics, particularly in integer operations, remains a common problem in the learning process. Students often experience difficulties in understanding abstract mathematical concepts, resulting in low learning motivation, limited classroom participation, and unsatisfactory learning outcomes. Therefore, an appropriate learning medium is needed to help students understand integer operations in a more concrete and engaging way. This study aims to analyze the use of domino card media in improving learning outcomes on integer operations among elementary school students based on previously published studies. The research employed a Systematic Literature Review (SLR) method. Data were collected through a review of relevant articles published in accredited national journals and scientific proceedings. The selected articles were analyzed and synthesized to obtain comprehensive information regarding the effectiveness of domino card media in mathematics learning. The findings indicate that domino card media is effective in teaching integer operations at the elementary school level. The use of this learning medium increases students' learning motivation, classroom participation, conceptual understanding, and computational skills. In addition, the learning process becomes more interactive and enjoyable, enabling students to better understand mathematical concepts. Based on the synthesis of the reviewed studies, domino card media has significant potential to improve mathematics learning outcomes, particularly in integer operations among elementary school students.